PERAN JASA FREIGHT FORWARDER DALAM MENUNJANG KESUKSESAN AKTIVITAS EKSPOR MELALUI TRANSPORTASI LAUT DI INDONESIA - Julian Arya Dwiguna; Rani Sukmadewi; Vhirda Daniyati Haryanto (POLITEKNIK LP3I JAKARTA, 2024)
Indonesia is one of the countries with the largest population in the world. With such a significant total population, the economic growth of its people is also expected to increase substantially. International trade plays a central role in driving global economic growth. Export, as one of the main pillars of international trade, makes a significant contribution to national income while accelerating economic growth. Freight forwarders play a vital role in facilitating these highly complex export activities. This research aims to analyze the role of freight forwarder services in supporting the success of export activities via sea transportation at PT. Freight Solution Indonusa. The research method used is qualitative descriptive, with data collection techniques through interviews and observations. The results show that PT. Freight Solution Indonusa has proven capable of contributing to export activities by responsibly handling the entire process of transporting goods, including shipment, document management, and customs clearance. Shipping via sea transportation has become the backbone of international trade due to the numerous advantages it offers exporters, such as lower logistics costs and cargo flexibility. With the increasing export activities in Indonesia, competition among logistics companies is becoming more competitive. PT. Freight Solution Indonusa needs to improve and evaluate its role as a freight forwarding company to maintain or even enhance the quality of its services.